FAKTOR IDIOSYNCRATIC RAUL CASTRO DALAM PERUBAHAN HUBUNGAN LUAR NEGERI KUBA-AMERIKA SERIKAT - Muhamad Bayu Saputra (Global Political Studies Journal, 2018)
The purpose and goal of this research is to know what the response taken by the US government to Raul Castro, the changes in the foreign relations of both countries, presence idiosyncratic factors of Raul Castro to the foreign relations of both countries. The method used is descriptive analysis techniques. Most of the data collected through literature and website searches. These results indicate that the factor of idiosyncratic Raul Castro in changes in foreign relations between Cuba and the United States. The conclusion from this study is the change that occurs in the foreign relations between the two countries, the changes occurring in the country of Cuba after Raul became president of Cuba, as well as the response taken by the US government against the government of Raul Castro well with the reopening of diplomatic relations between both countries, and issued a foreign policy that is intended to drive the Cuban economy, the type of personality that is owned by Raul Castro based on idiosyncratic theory is influential